Sexual behaviors at home and abroad: an online survey of Canadian young adult travelers - Emmanuelle Gareau; Karen P. Phillips (BMC, 2022)
Abstract Background For young adults, travel- an accessible and aspirational experience- may be accompanied by high-risk lifestyle behaviors abroad, which in turn, increases the risk of sexually transmitted and blood-borne infections (STBBI). This study aimed to examine sexual and risk behaviors of young Canadian adults both at-home and during international travel. Methods Sexually-active Canadians, aged 18-25 years (N = 646) who travelled abroad in 2016, completed an online, cross-sectional survey analyzed by descriptive statistics. Outcome measures included young Canadian adults' lifestyle risk and sexual behaviors at-home and abroad. Results Sexual behaviors, both penetrative and non-penetrative activities, decreased significantly (p < 0.001; McNemar test) abroad compared to at-home. International travel elicited a statistically significant increase in alcohol consumption compared to at-home (Wilcoxon, z = − 11.341, p < 0.001). Partner type (new trip-acquired partner) abroad was associated with a greater number of travel-acquired sexual partners (Mann-Whitney, U = 4901, p < 0.001), inconsistent condom use during penetrative sex (U = 7215, p = 0.009), and sex under the influence of alcohol (Test of Two Proportions, p < 0.001). Conclusions Although many young Canadian respondents practiced abstinence in their 2016 travel, for sexually-active travelers, new partner-type was related to high risk sexual behaviors. Young Canadians exhibited sexual risk behaviors both at-home and while travelling; suggesting the need for both domestic and pre-travel sexual health interventions.